2022
DOI: 10.1051/0004-6361/202142070
|View full text |Cite
|
Sign up to set email alerts
|

Probing inner and outer disk misalignments in transition disks

Abstract: Context. Transition disks are protoplanetary disks with dust-depleted cavities, possibly indicating substantial clearing of their dust content by a massive companion. For several known transition disks, dark regions interpreted as shadows have been observed in scattered light imaging and are hypothesized to originate from misalignments between distinct regions of the disk. Aims. We aim to investigate the presence of misalignments in transition disks. We study the inner disk (<1 au) geometries of a sample of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 161 publications
5
54
1
Order By: Relevance
“…Narrow "shadow" features have been observed along the outer disk cavity wall, suggesting that this inner disk may be inclined with respect to the outer disk (Marino et al 2015). Bohn et al (2022) provided the first resolved measurements of the inner disk using VLTI/GRAVITY observations, which they used to investigate the mutual alignments of the inner and outer disk components. They found that the K-band complex visibilities of their data were best fit by an inner disk model with an inclination of i d,inn = 23°.76 ± 3°.…”
Section: = -+mentioning
confidence: 99%
See 2 more Smart Citations
“…Narrow "shadow" features have been observed along the outer disk cavity wall, suggesting that this inner disk may be inclined with respect to the outer disk (Marino et al 2015). Bohn et al (2022) provided the first resolved measurements of the inner disk using VLTI/GRAVITY observations, which they used to investigate the mutual alignments of the inner and outer disk components. They found that the K-band complex visibilities of their data were best fit by an inner disk model with an inclination of i d,inn = 23°.76 ± 3°.…”
Section: = -+mentioning
confidence: 99%
“…We determine the posterior distribution of mutual inclinations between the binary orbit and both the inner and outer disk components (shown in Figure 15) by drawing random samples from the posterior distribution of i å and Ω å produced by orbitize!, and assuming a Gaussian distribution for the disk orientation centered on the values most recently inferred from ALMA gas kinematic data for the outer disk (i disk,outer = 38°.21 ± 1°.38, Ω disk,outer = 162°.72 ± 1°. 38; Perez et al 2015;Boehler et al 2017;Bohn et al 2022), and VLTI/GRAVITY observations for the inner disk (i disk,inner = 23°.76 ± 3°.18, Ω disk,inner = 15°.44 ± 7°.44; Bohn et al 2022).…”
Section: Mutual Inclinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution sub-mm continuum observations with ALMA have beautifully exposed a large-scale warp in GW Ori (Kraus et al 2020;Bi et al 2020), whose triple ring system is seen as a projected ellipses with different inclinations. Gravity Collaboration et al (2021) detected clear misalignments between both disks for 4 objects out of 9 transition disks, while Bohn et al (2022) detected additional misalignments in 6 targets out of sample of 20 transition disks. For 3 of those targets the orientation of the inner disk is consistent with the shadows detected in scattered light in the outer disks.…”
Section: Misaligned Inner Disks Radial Flows and Kinematics Of Transi...mentioning
confidence: 98%
“…The observations used in this work are summarised in Table 2. All are new to this work, with the exception of program 098.C-0760 (2017-10-06) which is presented in Appendix E of Bohn et al (2022). Together, they represent all currently available ESO high-contrast imaging data for CQ Tau.…”
Section: Observations and Data Reductionmentioning
confidence: 99%